Morality and religion : some reflections - Chattopadhyay, Uma; Banerjee, Aparna; Mitra, Shilpita; University of Calcutta. Department of Philosophy (Kolkata : University of Calcutta, Department of Philosophy under UGC SAP DRS (Phase 1) in collaboration with Mahabodhi Book Agency, 2012)
Contributed research papers.
Includes bibliographical references and index.
Includes passages in Sanskrit (Latin).
Keywords: RELIGIOUS ETHICS -- INDIA; RELIGION AND ETHICS; FAITH; INDIA -- RELIGION